(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Human resource management is the coordination of activities to find, develop, maintain, manage and facilitate human resources to operate through the organization, in order to achieve the goals and direction of the organization. The important requirements of human resource management is to find the right people, in the right quantity and at the right time with conditions that satisfy both the business and the applicant. When choosing the right candidate for the right position, both individual and business benefit. Human resource management plays an essential role in the existence and development of enterprises. This is reflected in the factors that help a business operate well or not, succeed or fail, thanks to the people who are working at the enterprise with creativity, passion and love. Humans are invaluable assets for businesses, as technical machines and material possessions can be bought and copied, but people cannot.